ON THE ISSUE OF ASSESSING THE ECOLOGICAL STATE OF VARIOUS WATERCOURCES IN THE CONDITIONS OF ANTHROPOGENIC PRESSURE - Elena A. Shashulovskaya; Svetlana A. Mosiyash; Olga V. Shashulovskaya; Irina G. Filimonova; Liliya V. Grishina; Elena G. Kuzina (Водное хозяйство России: проблемы, технологии, управление)
An assessment is given of the ecological state of nine rivers with different levels of anthropogenic load related to the Volga, the Don and the Ural basins. The water quality was assessed on the basis of several indices: the widely used specific combinatorial water pollution index (SCWPI), and statistical criteria based on the data of long-term environmental monitoring: the plasticity indicator as a measure of ecosystem sustainability and the desirability function. Hydro/chemical studies included indicators of oxygen regime, salt composition, organic matter, biogenic and toxic elements. The calculated SCWPI fluctuated in the range of 3,0–5,4, which corresponds to the quality category “very polluted” - “dirty”. The water of the lowest quality is in the small rivers Berezina and Elshanka, part of which is located in the industrial zone of the city of Saratov. The greatest contribution to the assessment of the degree of water pollution is made not only by the concentration of technogenic metals, but also by indicators of the content of organic matter, the amount of which depends on the level of bioproduction processes. The principal component analysis made it possible to structure the indices calculated for each river and to “explain” some of the information contained in the initial variables. Two main components were selected, based on the analysis results. The first factor integrates a negative relationship between the value of the UCIPI and the length of the river. Large rivers are more resistant to pollution due to their high water content. The second factor incorporated environmental criteria – the desirability function and the plasticity indicator, i.e. statistical indicators based on the data of long-term hydro/chemical monitoring and taking into account the real ecological state –“health” of natural water systems and their sustainable functioning. Cluster analysis of the obtained statistical indices made it possible to divide the studied rivers by the quality of the aquatic environment into 4 groups.